KESEPIAN DAN KEINGINAN MELUKAI DIRI SENDIRI REMAJA - Diana Savitri Hidayati; Elda Nabiela Muthia (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
In the past few years, suicide cases are increasing in Indonesia. There is a probability that self-injury may be done before someone commits a suicide. An ideation is formed before someone does self-injury, which is used as a way to solve problems. There are few reasons as to why someone thinks about doing self-injury, internally or externally, and one of those reasons is loneliness. The main purpose of this study is to define the relationship between loneliness and deliberate self-injury ideation –the thoughts teenagers have regarding self-injury. Using accidental non-random sampling technique, 316 participants from both gender are taken from a senior high school in Balikpapan, East Kalimantan. Instruments used in this study are ESLI (Emotional-Social Loneliness Inventory) and NSSI Ideation Questionnaire. Result shows a very significant correlation between both variables (sig = 0.000) with correlation r = 0.274.